Successful repair of intraoperative cerebrospinal fluid leaks improves outcomes in endoscopic skull base surgery. Issue 1 (31st August 2016) - Shahangian, Arash; Soler, Zachary M.; Baker, Andrew; Wise, Sarah K.; Rereddy, Shruthi K.; Patel, Zara M.; Oyesiku, Nelson M.; DelGaudio, John M.; Hadjipanayis, Constantinos G.; Woodworth, Bradford A.; Riley, Kristen O.; Lee, John; et al.
Abstract : Background: The impact of failed cerebrospinal fluid leak (CSF) leak repair in endoscopic skull base surgery has not been adequately studied. Methods: In this investigation we reviewed patients who had undergone endoscopic skull base surgery between 2002 and 2014 at 7 international centers. Demographic variables, comorbidities, tumor characteristics, and repair techniques were evaluated to determine association with successful repair of CSF leak. Postoperative complications and length of stay were compared among groups. Results: Data were collected on 2097 patients who were divided into 3 groups: (1) those with no intraoperative leak (n = 1533); (2) those with successful repair of their intraoperative leak (n = 452); and (3) those with failed repair (n = 112). Compared with successful repair, failed repair was associated with an increased risk of intracranial infection (odds ratio [OR], 5.6; 95% confidence interval [CI], 5.3‐13.15), pneumocephalus (OR, 16; 95% CI, 5.8‐44.4), 30‐day readmission (OR, 8.4; 95% CI, 5.3‐13.5), reoperation (OR, 115.4; 95% CI, 56.3‐236.8), and prolonged hospital stay (14.9 vs 7.0 days, p < 0.01). Outcomes in patients who had successful repairs of intraoperative leaks were similar to those who never had leakage. Intraoperative use of pedicled nasoseptal flaps was associated with successful repair (OR, 0.60; 95% CI, 0.34‐0.92). Conclusion: Intraoperative CSF leaks are a frequent and expected occurrence during endoscopic skull base surgery. Failed CSF leak repair has a significant impact on patient outcomes, with increased rates of postoperative pneumocephalus, intracranial infections, reoperation, deep vein thrombosis, readmission, and prolonged hospital stay. Recognition and repair of intraoperative CSF leaks reduces postoperative complications. Use of pedicled nasoseptal flaps improves outcomes in reconstructing defects at higher risk for postoperative leak.